Redefining Latin American Historical Fiction : the Impact of Feminism and Postcolonialism - Weldt-Basson, Helene Carol (Palgrave Macmillan, 2013)
Current scholarship on Latin American historical fiction hasfailed to take feminism and postcolonialism into account. This study uses theseimportant contemporary discourses as a starting point for a new definition of theLatin American historical novel that includes national identity, magical realism, historical intertextuality, and symbolism.